The Impact of Tax Digitalization and Tax Awareness on Compliance Among Taxpayers: a Study of Individual Taxpayers at KPP Pratama Badung Utara - Wahyuni, Ni Nyoman Tri; Smara, I.B Yogi; Ferreira, Pryty Dorce Mendonca (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study employs a quantitative methodology, utilizing statistical techniques and associative analysis to investigate the relationships among certain variables. Causal research, in contrast, seeks to determine the relationships typically characterized as causal, symmetrical, or interactive associations. The main objective of this study is to provide evidence regarding the effect of the independent variables-tax digitalization (X1) and tax knowledge (X2)-on the dependent variable, taxpayer compliance (Y). Data for this study was gathered via a survey, which involved distributing questionnaires to participants. The research commenced in June 2023, with a focus on individual taxpayers at KPP Pratama Badung Utara. Results: The findings of this research demonstrate that the digitization of the taxation process markedly enhances taxpayer compliance, as evidenced by a significance value of 0.000, which falls below the 0.05 threshold.